Nursing of a patient with herpes zoster treated by Traditional Chinese Medicine wet-hot compress technique (中药湿热敷技术治疗带状疱疹1例的护理体会) - ZHU Jinqing (朱进晴); SUN Mingli (孙明丽); RUAN Na (阮娜); TANG Ling (唐玲) (Association of Integrative Nursing, 2022)
In this paper, the effect observation and nursing measures of a case of herpes zoster patient treated by Chinese herbal medicine wet-hot compress technique were summarized. The wet-hot compress technique was conducted under the guidance of Traditional Chinese Medicine (TCM) syndrome differentiation and nursing theory, and corresponding nursing interventions such as nursing assessment, basic nursing and emotional care were carried out to relieve the pain and shorten the time of wound healing. (本文回顾1例带状疱疹患者行中药湿热敷治疗的效果, 总结护理措施。在中医辨证施护理论指导下, 采取中药湿热敷技术, 同时完善护理评估、常规护理、情志护理等, 能有效改善疼痛症状, 促进疱疹消退和皮损结痂。)